Empty container repositioning strategy in intermodal transport with demand switching. (April 2019) - Luo, Tian; Chang, Daofang
Highlights: We study empty container repositioning problem with customer demand switching. We model an empty container repositioning problem with unidirectional transshipment. We prove the existence of unique Nash equilibrium of the stochastic inventory game. Repositioning price is a key factor affecting the empty container inventory level. We apply contract coordination theory to the empty container repositioning problem. Abstract: In this paper, we study the empty container inventory repositioning problem with customer demand switching in intermodal transport. The objective of this article is to solve the empty container repositioning problem by contract coordination theory, and to improve the coordination of empty container management and the profit of each participant. We consider an intermodal transport system composed of the rail firm and the liner firm. First, we have considered the situation of no cooperation between the dry port and the seaport, and established a model where there is only the customer demand switching without the occurrence of empty container repositioning. Next, we consider the cooperation between the dry port and the seaport in the decentralized model and the centralized model, and set up the empty container repositioning models from the seaport to the dry port respectively. We analyse the optimal inventory level for the dry port and the seaport under different models, and the effect of the repositioning price on the optimal inventory level. We then apply the contract coordination theory to the empty container inventory repositioning problem. We propose an inventory coordination strategy based on a revenue sharing contract and coordinate the intermodal transport system by choosing the appropriate contract parameters. The results of the study show that under the guidance of the seaport, the revenue sharing contract can achieve a win-win situation for the dry port and the seaport.